Who argues better?: Schemes and argumentative quality in Chilean elderly and young people - Santibáñez, Cristián; Gascón, José (Círculo de Lingüística Aplicada a la Comunicación, 2020)
In this paper, the argumentative quality of elderly people and young Chilean university students is analysed comparatively. Using the notion and types of argumentative schemes proposed by the integrated theory of argumentative structure (Marraud, 2013), the production of arguments of both groups giving their opinion on a moral dilemma is characterized. Among the main findings, it should be emphasized that the percentages of simple arguments and complex arguments in both groups are strikingly similar. Elderly people argue with a level of complexity equivalent to that of the young people (university students) interviewed. On the other hand, it is interesting to see that elderly people make greater use of end-to-means arguments, while young people rely to a greater extent on arguments based on rules and norms.